Peran Kepemimpinan Strategis dalam Meningkatkan Daya Saing Sekolah: Sebuah Tinjauan Literatur Komparatif (2021-2025) - Ramdan Ramdan; Atikah Atikah; Islahiyah Islahiyah; Detia Detia; Budi Ilham Maliki (Riviera Publishing, 2026)
Changes in the increasingly dynamic educational environment require schools to increase competitiveness through adaptive and strategic leadership. Strategic leadership is an important factor in determining the direction, quality, and sustainability of educational institutions in the midst of increasingly fierce competition. This study aims to analyze and compare the literature on the role of strategic leadership in increasing school competitiveness in the 2021–2025 period. This study uses a qualitative approach with a comparative literature review method. Data were obtained from various relevant scientific journal articles and analyzed using qualitative descriptive techniques through the stages of data reduction, data presentation, and conclusion drawn. The analysis focused on the concept of strategic leadership, school competitiveness factors, and strategies used in improving the quality of education. The results of the study show that strategic leadership plays a significant role in increasing school competitiveness through several key aspects, namely visionary and adaptive leadership, human resource development, digital transformation, strengthening organizational culture, stakeholder involvement, and data-based decision-making. School competitiveness is influenced by various interrelated factors, such as teacher quality, learning innovation, educational facilities, and public reputation and trust. The conclusion of this study confirms that strategic leadership is the main pillar in creating a sustainable school competitive advantage. Therefore, it is necessary to strengthen leadership capacity, use technology, and effective collaboration to improve the quality of education. These findings are expected to be a reference for practitioners and researchers in developing more adaptive and innovative leadership strategies in the future